Hubungan Faktor Internal dengan Pola Pemberian ASI di Puksesmas Putat Jaya Surabaya - Elsenja Putri Pawaris (Lembaga Pengembangan Kinerja Dosen, 2025)
Exclusive breastfeeding for the first six months of an infant's life is an important practice that supports child growth and development. The purpose of this study was to examine the relationship between internal maternal factors and breastfeeding patterns. The study was conducted using a cross sectional study design. The study was conducted at Puskesmas Putat Jaya Surabaya with a sample of 63 mothers with infants <6 months who provide direct breastfeeding to their babies. Data were obtained from questionnaires, weight measurement using digital scales and height using microtoice. Data were processed using chi square test. The test results showed that there was a significant relationship between maternal knowledge with proper colostrum feeding (p = 0.002), parity with breastfeeding frequency (p = 0.002) and maternal nutritional status with breastfeeding frequency (p = 0.001). While other variables in this study showed no significant relationship. It can be concluded that there is a relationship between maternal knowledge and proper colostrum feeding and there is a significant relationship between parity and nutritional status with the frequency of breastfeeding. Suggestions for the need for education as an increase in knowledge and maintaining a diet to increase the success of breastfeeding.